Duodenal microbiota makes an important impact in functional dyspepsia. (January 2022) - Zheng, Yi-Feng; Liang, Shu-Ping; Zhong, Zi-Shao; Zhang, Wang; Wu, Yu-Yao; Liu, Jia-Bin; Huang, Sui-Ping
Abstract: Duodenal microbiota may have impact in Functional Dyspepsia. The aim of this study was to explore the difference of microbiota on duodenal mucosa between patients with Functional Dyspepsia and normal subjects. The duodenal mucosa of the subjects were collected under upper gastrointestinal endoscope and the contents of the descending duodenal intestine were extracted with cell brushes in 20 patients with Functional Dyspepsia and 5 healthy subjects. The microbiome on duodenal was studied by 16SrDNA gene sequencing. The differences of duodenal flora were analyzed and compared by LEfSe, FAPROTAX, SPSS and other software. There were significant differences in ACE index, shannon index and observedspecies index between patients with functional dyspepsia and healthy people ( P < 0.05). PCoA analysis of the structure of bacteria between two groups found that the duodenal microbiome showed a separate trend. In further study, Amova analysis showed a significant difference ( P < 0.05). We found that the there are obvious differences in the composition of duodenal microbiome in functional dyspepsia and healthy people. At the genus level, there were significant differences in Alloprevotella, Peptostreptococcus, Sutterella, Corynebacteriurn, Catonella, Faecalibacterium, Staphylococcus, Eubacteriumnodatumgro-up, Lachnoclostridiurn and Lautropia between the two groups (P < 0.05). The prediction results of Microflora function from FAPROTAX showed that the urea decomposing (ureolysis) and fumaric acid respiratory (fumaraterespiration) function of duodenal bacteria in patients with functional dyspepsia were significantly different from those in healthy people (P < 0.05). In conclusion, there is a significant difference in mucosal microflora of duodenum between patients with functional dyspepsia and healthy groups. It includes greater microflora diversity, different microflora structure, different microflora composition, specific taxa and specific microbiome function. The disorder of duodenal microecology may be the formation mechanism of functional dyspepsia. Highlights: Previous studies on FD paid little attention to duodenum, especially the relationship between duodenal microflora. However, due to the location of duodenum and the difficulty of gastroscopic operation, there are few studies on duodenum. In this study, we studied the differences of duodenal microflora in patients with FD and healthy people, and predicted the function of duodenal microflora in order to verify the relationship between FD and duodenal microflora. Thus, To provide evidence for probiotics in the treatment of functional dyspepsia. The duodenal mucosa of the subjects were collected under upper gastrointestinal endoscope and the contents of the descending duodenal intestine were extracted with cell brushes in 20 patients with Functional Dyspepsia and 5 healthy subjects. The microbiome on duodenal was studied by 16SrDNA gene sequencing. The differences of duodenal flora were analyzed and compared by LEfSe, FAPROTAX, SPSS and other software. There were significant differences in ACE index, shannon index and observedspecies index between patients with functional dyspepsia and healthy people. PCoA analysis of the structure of bacteria between two groups found that the duodenal microbiome showed a separate trend. In further study, Amova analysis showed a significant difference. The prediction results of Microflora function from FAPROTAX showed that the urea decomposing (ureolysis) and fumaric acid respiratory (fumaraterespiration) function of duodenal bacteria in patients with functional dyspepsia were significantly different from those in healthy people. In conclusion, there is a significant difference in mucosal microflora of duodenum between patients with functional dyspepsia and healthy groups. It includes greater microflora diversity, different microflora structure, different microflora composition, specific taxa and specific microbiome function. The disorder of duodenal microecology may be the formation mechanism of functional dyspepsia.